Introduction to hybrid vehicle system modeling and control - Liu, Wei, 1960 August 30- (Hoboken : John Wiley & Sons, 2013)
This is an engineering reference book on hybrid vehicle system analysis and design, an outgrowth of the author's substantial work in research, development and production at the National Research Council Canada, Azure Dynamics and now General Motors. It is an irreplaceable tool for helping engineers develop algorithms and gain a thorough understanding of hybrid vehicle systems. This book covers all the major aspects of hybrid vehicle modeling, control, simulation, performance analysis and preliminary design. It not only systemically provides the basic knowledge of hybrid vehicle system confi.
Introduction -- Basic components of hybrid vehicle -- Hybrid vehicle system modeling -- Power electronics and electric motor drives of hybrid vehicle -- Energy storage system modeling and control -- Energy management strategies of hybrid vehicle -- Other hybrid vehicle control problems -- Plug-in charging characteristics, algorithm, and impact on power distribution system -- Hybrid vehicle design and performance analysis -- Appendix A: System identification: state and parameter estimation techniques -- Appendix B: Advanced dynamic system control techniques -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Hybrid electric vehicles -- Simulation methods; Hybrid electric vehicles -- Mathematical models; TRANSPORTATION -- Automotive -- Antique & Classic; Electronic books